On the lacunary $(A, ϕ)$ -statistical convergence of double sequences - Savaş, E. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We extend some results known from the literature for ordinary (single) sequences to multiple sequences of real numbers.Further, we introduce a concept of double lacunary strong $(A, ϕ)$-convergence with respect to a modulus function. Inaddition, we also study some relationships between double lacunary strong $(A, ϕ)$-convergence with respect to a modulusand double lacunary statistical convergence.